Rethinking Psychiatric Terror against Nationalists in Ukraine: Spatial Dimensions of Post-Stalinist State Violence - Bertelsen, Olga (Kyiv-Mohyla Humanities Journal, 2014)
This study focuses on psychiatric terror in the Soviet Union in the 1960s–1980s applied to nationalists who constituted approximately one-tenth of those who fell victim to political psychiatry. More specifically, through the spatial examination of two Ukrainian psychiatric clinics’ practices and the individual history of the Ukrainian dissident Victor Borovsky, this study analyses the effectiveness of silence that surrounded the cases of “psychiatric patients” in the context of increasing discontent in the republic and the national liberation movement. The medicalization of social control, psychiatric abuses, state violence and brutality exacerbated non-violent popular resistance in Ukraine, which culminated in political activism of Ukrainian patriots in the late 1980s, contributing greatly to the collapse of the Soviet Union and the emergence of independent Ukraine. Despite these ultimate outcomes, forced silence through psychiatric terror was an effective tool in the Soviet arsenal of suppression.